The importance of metabolomics in research into pathological processes leading to neurodegenerative diseases - Wajda, Katarzyna; Mika, Wiktoria; Słowik, Justyna; Sieradzka, Izabela (Journal of Education, Health and Sport, 2025)
Objective: The aim of this article is to review and analyse the current state of knowledge on the role of metabolomics in explaining the pathological processes underlying neurodegenerative diseases, in particular Alzheimer's, Parkinson's and Huntington's diseases. The analysis focuses on assessing the potential of this field in discovering early diagnostic biomarkers and identifying new therapeutic targets. Materials and methods: A systematic review of the scientific literature was conducted using the PubMed, Scopus and Web of Science databases. The analysis included studies using mass spectrometry (MS) and nuclear magnetic resonance (NMR) spectroscopy to profile metabolites in biological fluids (cerebrospinal fluid, plasma) and brain tissue from patients and preclinical models. Results: Neurodegenerative diseases are characterised by common metabolic disorders, such as mitochondrial dysfunction, impaired energy metabolism and oxidative stress. Disease-specific signatures have also been identified: xanthine metabolism disorders and impaired kynurenine pathway in Parkinson's disease, dysregulation of lipid (including ceramide and sphingolipid) and glucose metabolism in Alzheimer's disease, and early changes in the tryptophan/kynurenine pathway in Huntington's disease. Conclusions: This work highlights the role of metabolic dysregulation as an early mechanism in the pathogenesis of Alzheimer’s, Parkinson’s, and Huntington’s diseases. Metabolomics enables a systemic view of these disorders as disruptions of complex metabolic networks, providing a comprehensive picture of pathology rather than focusing on individual proteins. Its clinical potential includes the development of non-invasive biomarkers for early diagnosis and disease monitoring. Identification of key metabolic pathways, such as lipid and energy metabolism, also points to new therapeutic targets, forming the basis for precision medicine in neurodegenerative diseases.